Mekanisme Perilaku Individu dalam Respons Kebijakan Fiskal: Mental Accounting, Pertumbuhan Ekonomi dan Kenaikan Tarif Pajak Pertambahan Nilai - Hilda Putri Aprilia; Nugroho Wisnu Murti (STIE AUB Surakarta, 2025)
This study examines the role of mental accounting in the relationship between a Value-Added Tax (VAT) rate increase and consumer purchasing power (a key driver of economic growth). Surveying an academic community, this study find mental accounting does not moderate this relationship in the full sample. Contrary to classical theory, the VAT increase is associated with higher purchasing power, a finding more consistent with scarcity theory. Nevertheless, split-sample analysis reveals a nuanced dynamic. Mental accounting emerged as a significant moderating variable, but its effects operated in opposite directions depending on gender. These results demonstrate the complex behavioral responses to fiscal policy and highlight the need for policy design that accounts for individual heterogeneity to ensure targeted effectiveness.